The Progression of Posterior Cortical Atrophy to Corticobasal Syndrome: Lumping or Splitting Neurodegenerative Diseases? - Giorelli, Maurizio (Columbia University Libraries/Information Services, 2014)
BACKGROUND: Posterior cortical atrophy is a clinical syndrome that is characterized by the progressive loss of visuospatial integration and is associated with neurodegenerative conditions. CASE REPORT: We describe a 60-year-old female with simultanagnosia, oculomotor apraxia, and optic ataxia for which she received an initial clinical diagnosis of posterior cortical atrophy. Three years later, she developed Balint's syndrome, Gerstmann's syndrome, left alien hand syndrome, smooth asymmetric (left) rigidity, cortical sensory loss, and spontaneous myoclonic jerks of the left arm, which suggested a final diagnosis of corticobasal syndrome. DISCUSSION: This case report indicates that corticobasal syndrome may present with visuospatial deficits.